2021
DOI: 10.1021/acsami.1c01898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Exposure of ZnMgO Nanoparticle Electron Transport Layer on Efficiency of Quantum-Dot Light-Emitting Diodes

Abstract: We demonstrate the effect of air exposure on optical and electrical properties of ZnMgO nanoparticles (NPs) typically exploited as an electron transport layer in Cd-based quantum-dot light-emitting diodes (QLEDs). We analyze the roles of air components in modifying the electrical properties of ZnMgO NPs, which reveals that H 2 O enables the reduction of hole leakage while O 2 alters the character of charge transport due to its ability to trap electrons. As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…The characteristics show little current leakage below 2 V, less than 0.1 mA cm À2 , indicating that the ZnMgO layer here is 'optimal', with similar behavior as aged films. 37,38 The full-cycle sweep shows that electron injection improves in the returning half-cycle. This hysteresis is characteristic of the ZnMgO contact but often neglected in the literature.…”
Section: Excited-state Lifetime Measurementsmentioning
confidence: 99%
“…The characteristics show little current leakage below 2 V, less than 0.1 mA cm À2 , indicating that the ZnMgO layer here is 'optimal', with similar behavior as aged films. 37,38 The full-cycle sweep shows that electron injection improves in the returning half-cycle. This hysteresis is characteristic of the ZnMgO contact but often neglected in the literature.…”
Section: Excited-state Lifetime Measurementsmentioning
confidence: 99%
“…According to Chrzanowski et al, [ 108 ] lifetime measurements revealed that the air‐exposed devices could exhibit much‐improved operational stability (Figure 17e). Two different regimes were identified: Repeating scans under 3 V resulted in reproducible performance, but scanning up to 6 V quickly irreversibly degraded the device performance (Figure 17f).…”
Section: Modification Methods For Zno‐based Electron Transport Layer ...mentioning
confidence: 91%
“…Chrzanowski et al reported controlled (humid) air exposure of ZnO‐based ETLs as a suitable approach to improve the charge balance in their QLEDs. [ 108 ] The authors investigated the effect of water and oxygen on the carrier density in the ETL. It was observed that exposure of the ZnMgO ETL to humid air at room temperature resulted in reduced hole leakage and improved charge balance in the device.…”
Section: Modification Methods For Zno‐based Electron Transport Layer ...mentioning
confidence: 99%
“…Quantum light-emitting diodes (QLEDs) have triggered a tremendous increase in research interest in recent years since the discovery of cadmium selenide nanocrystal-based QLEDs, , and they are expected to be one of the mainstream next-generation display technologies. One of the core techniques in QLEDs is the use of inorganic nanoparticles to substitute the traditional organic molecules as the electron transport layer (ETL) to achieve color controllability and purity, narrow full-width at half-maximum (fwhm) emission wavelength, and long lifetime. ZnO nanoparticles (NPs) are the most widely used ETL, mainly because of their high electron mobility, strong coupling effect, and conductive band edge matched with that of the emissive layer (EML), which enables the excellent injection of electrons from ZnO NPs to the emissive layer. However, the low hole mobility of the organic hole transport layer (HTL) does not match the high electron mobility in the ETL layer, resulting in the unbalanced injection of electrons and holes to the EML and the excessive accumulation of electrons in the EML, which degrades the performance and lifetimes of the QLEDs .…”
Section: Introductionmentioning
confidence: 99%